Compost environmental protection standards in Canada. Issue 3 (1st May 2006) - Ge, Bo; McCartney, Daryl; Zeb, Jehan
Abstract : The purpose of this paper was to summarize and compare Canadian environmental protection standards for compost. The paper describes the national and provincial organizations responsible for compost quality control in Canada. Discussions were organized under the key environmental protection criteria: maturity, trace elements, time–temperature requirements, pathogens (indicator organisms), foreign matter, and trace organics. A total of six organizations (three across Canada and three provincial) currently have distinct standards. Recent efforts to harmonize the standards have reduced the disparity between the various organizations. Key words : compost, Canada, standards, environmental protection, criteria, solid waste management.